Development and evaluation of case video-based debriefing on a simulation of high-risk neonatal care for nursing students in South Korea: a mixed-methods study - Hyun Young Koo; Bo Ryeong Lee; Hyeran An (BMC, 2023)
Abstract Background The debriefing process after health care simulations should provide a psychologically safe learning environment for nursing students. Case video-based debriefing on a simulation of high-risk neonatal care can help nursing students feel psychologically safe and make learning more effective. In this study, we developed case video-based debriefing materials for a simulation of high-risk neonatal care for nursing students in South Korea and evaluated their effects. Methods This mixed-methods study, consisting of a survey and an in-depth interview, was conducted between August and December 2022. The participants were 27 nursing students for the development of the case video-based debriefing and 51 nursing students for the evaluation of its effects (25 in the experimental group and 26 in the control group) at a university in South Korea. A case video-based debriefing on a simulation of high-risk neonatal care was developed, and the experimental group took part in case video-based debriefing. The participants' self-efficacy, critical thinking, state anxiety, and satisfaction with practice were examined. The experimental group's learning experiences were explored. Quantitative data were analyzed using the chi-square test, the unpaired t-test, and repeated-measures analysis of variance. Qualitative content analysis was conducted. Results In the experimental group, critical thinking and satisfaction with practice increased to a greater extent than in the control group. However, the changes in self-efficacy and state anxiety were not significantly different between the experimental and control groups. Four categories were extracted from nursing students who participated in the case video-based debriefing: "learning facilitated by the simulation," "expanded learning," "safe learning environment," and "efficient utilization of case videos." Conclusions Case video-based debriefing on a simulation of high-risk neonatal care effectively enhanced nursing students' critical thinking and satisfaction with practice, and it will be utilized to improve nursing students' competency in high-risk neonatal care.